ANALISIS HUTANG JANGKA PENDEK DAN HUTANG JANGKA PANJANG TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sidabutar, Marantika; Wage, Sunarto (SCIENTIA JOURNAL, 2021)
This research is shown to analyze the current ratio and debt to asset ratio against the financial performance of Manufacture Company listed on the Indonesia Stock Exchange. The population in this study were all food and beverage company listed on the Indonesia Stock Exchange, namely 26 companies and using a sample of 7 according to the criteria set in the sample. The research instrument is documentation and uses secondary data sources obtained from said companies financial reports listed on the Indonesia Stock Exchange. The data analysis technique used in this research is statistical test with classic assumption test in the form of normality test, multicollinearity test, heterocedacity test and autocorrelation test and using multiple linear regression test consisting of t test and F test, using SPSS version 25 F in this study shows that the variables current ratio and debt to asset ratio together have an effect on return on assets. The results of the partial test on this research is H1 with value at t 1,156 < 2.13185 which means Return on Asset is not affected by current ratio and H2 with value at -9,060 < 2.13185 which also means debt to asset ratio is not affecting return on asset. lastly, on F test, H3 having its value at 42,555 > F table 6,59, which means current asset and debt to asset ratio simultaneosly not affecting return on asset.